Pengaruh Company Size dan Environmental Performance Terhadap Pengungkapan lingkungan - Kusumawardhani, Indira; Suhartini, Dwi (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This Research aims to examine and prove the effect of Company Size and Environmental Performance on Environmental Disclosure by using a quantitative method. This research topic is very important to study in analyzing the extent to which mining companies fulfill their obligations to carry out Environmental Disclosure in accordance with OJK Regulation No. 51 of 2017. The sampling method uses purposive sampling with a total sample of 65 data from 13 Mining Companies Listed on the BEI for the 2017-2021 period. Multiple linear regression was used to analyze the data with the Eviews 12 software. The results of this study prove that mining companies listed on the BEI already have a responsibility for environmental disclosure which is driven by the large size of company assets owned and environmental performance. In addition, there is evidence that mining companies listed on the BEI have not fully reported environmental disclosure based on GRI standards. The company only reported 12 of the 32 required indicators or around 37.64%. Keywords: Pengungkapan lingkungan, Company Size, Environmental Performance